ANALYSIS OF RISK FACTORS AND TREATMENT PHASES ON THE SEVERITY OF HEPATOTOXICITY DUE TO ANTI-TUBERCULOSIS DRUGS - Nazhipah Isnani; Samsul Hadi; Dita Aulia Dwi Sandi; Satrio Wibowo Rahmatullah; Wirawan Adikusuma; Reni Yustiati Saksono; Najma Auralia; Khelda Maulida; Feri Setiawan (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2026)
Hepatotoxicity caused by anti-tuberculosis drugs (OAT) is one of the adverse effects of tuberculosis therapy and may lead to liver dysfunction. This study aimed to analyze the relationship between age, gender, and treatment phase with the severity of OAT induced hepatotoxicity, as well as to assess factors influencing the increase in hepatotoxicity grade. This research employed a retrospective cross-sectional design and was conducted at Ulin Regional Hospital Banjarmasin using a total sampling method involving 45 tuberculosis patients. Secondary data were obtained from medical records of TB patients in 2024–2025. The results showed that 62.2% of patients were under 60 years old and 37.8% were over 60 years old. Male patients accounted for 75.6%, while females accounted for 24.4%. The distribution of hepatotoxicity grades was 40% normal, 28.9% grade 1, 20% grade 2, and 11.1% grade 3. Based on the treatment phase, 91.1% of patients were in the intensive phase and 8.9% were in the continuation phase. The Chi square test revealed no significant association between age, gender, or treatment phase and the severity of hepatotoxicity.